A rare presentation of KBG syndrome - Mohan, Dhanya Soodhana; Nagarajappa, Vani Hebbal (International Journal of Contemporary Pediatrics, 2021)
KBG syndrome is a rare, genetic disorder characterizedby cognitive impairment, short stature, skeletal (mainly costovertebral) anomalies and a distinct craniofacial appearance. It is usually autosomal dominant in nature with a wide range of expressivity in its clinical features. We describe what appears to be the third case reported from India.The aim of this article is to review familiar clinical features and to highlight the endocrine management of KBG syndrome. We are hereby reporting a case of 17 year 10 months old adolescent who had neurocognitive impairment and a characteristic appearance, which led to the diagnosis of this genetic condition.